Effects of Gender on Outcomes and Survival Following Repair of Acute Type A Aortic Dissection - Conway, Brian D.; Stamou, Sotiris C.; Kouchoukos, Nicholas T.; Lobdell, Kevin W.; Hagberg, Robert C. (International Journal of Angiology, 2015)
Previous studies have demonstrated gender-related differences in early and late outcomes following type A dissection diagnosis. However, it is widely unknown whether gender affects early clinical outcomes and survival after repair of type A aortic dissection. The goal of this study was to compare the early and late clinical outcomes in women versus men after repair of acute type A aortic dissections.Between January 2000 and October 2010 a total of 251 patients from four academic medical centers underwent repair of acute type A aortic dissection. Of those, 79 were women and 172 were men with median ages of 67 (range, 20–87 years) and 58 years (range, 19–83 years), respectively (p < 0.001). Major morbidity, operative mortality, and 10-year actuarial survival were compared between the groups.Operative mortality was not significantly influenced by gender (19% for women vs. 17% for men, p = 0.695). There were similar rates of hemodynamic instability (12% for women vs. 13% men, p = 0.783) between the two groups. Actuarial 10-year survival rates were 58% for women versus 73% for men (p = 0.284).Gender does not significantly impact early clinical outcomes and actuarial survival following repair of acute type A aortic dissection.
Keywords: aortic dissection; repair; dissection; cardiac surgery